Does completion of radical hysterectomy improve oncological outcomes of women with clinical early-stage cervical cancer and intraoperative detection of nodal involvement?: protocol for a systematic review and meta-analysis. Issue 7 (29th July 2022) - Hu, Cui; Xu, Yu; Zhang, Qianwen; Liu, Qing; Du, Yi; Jia, Ya; He, Yue-Dong; Zheng, Ai; Xu, Hui; Cui, Shuang-Shuang; Tian, Yong; Ran, Lin; et al.
Abstract : Introduction: The management of women with clinical early-stage cervical cancer and lymph node involvement detected intraoperatively is heterogeneous and controversial. This paper presents the protocol of a systematic review and meta-analysis regarding the management of this specific population of patients. This proposed study aims to answer the question: does completion of radical hysterectomy improve the oncological outcomes of women with clinical early-stage cervical cancer and intraoperatively detected nodal involvement? Methods and analysis: This protocol is drafted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols guidelines, and the proposed study will be conducted in accordance with the standard guidelines of 'Preferred Reporting Items for Systematic Reviews and Meta-Analyses' and 'Meta-analysis of Observational Studies in Epidemiology reporting guideline'. Comprehensive literature searches will be performed in PubMed, Embase, Scopus, and Web of Science. The screening of the eligible studies, the extraction of data of interest, and the quality assessment of the included studies will all be independently performed by different members of our team. The primary outcome of this proposed study will be comparing the risk of recurrence or death from cervical cancer and the risk of all-cause death in patients with two different treatments (completion of radical hysterectomy or abandonment of radical hysterectomy); the secondary outcome of this proposed study will be comparing the risk of the grade 3/4 toxicities associated with the two types of management. Given the clinical heterogeneity among the included studies, data on outcomes will be pooled by random-effects models. Heterogeneity will be evaluated using the I 2 statistic. The risk of bias for the included studies will be evaluated using the Newcastle-Ottawa Scale or the Cochrane collaboration's tool. The grade of evidence will be evaluated by two independent members of our team using the Grading of Recommendations, Assessment, Development and Evaluations approach. Ethics and dissemination: Ethical approval is not required because there will no primary data collected. The findings of this proposed study will be published in an international peer-reviewed journal. PROSPERO registration number: CRD42021273527.